Increasing Motivation to Learn History Through the Team Games Tournament Model Assisted by Emoji Puzzle Card Media in Class XI-1 Students of SMA Negeri 5 Medan - Murlina*, Nia; Nasution, Abd. Haris; Nasution, Sovianur (Universitas Syiah Kuala, 2024)
This research aims to increase the motivation to learn history in class XI-1 students at SMA Negeri 5 Medan through the application of the Team Games Tournament (TGT) learning model assisted by emoji puzzle card media. The research method uses a qualitative approach with data collection techniques carried out through observation, motivation questionnaires and documentation. The research results showed that there was a significant increase in student learning motivation after implementing the TGT model with emoji puzzle card media. In cycle I, poor results were obtained with a percentage of 60%. In cycle II, the increase in motivation was increasingly visible with a percentage of 90%. In conclusion, the TGT model using emoji puzzle cards has proven successful in increasing students' motivation to learn history.